Financial frictions, capital reallocation, and aggregate fluctuations - Jürgen von Hagen; Haiping Zhang (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2006)
We address an important business cycle fact, i.e., the amplified and hump-shaped responses of output to productivity shocks, in a dynamic general equilibrium model with financial frictions. Models with financial frictions in the current literature have either the amplification mechanism or the propagation mechanism. Our model shows that the dynamic interaction of borrowing constraints, endogenous capital accumulation and capital reallocation among agents with different productivity constitutes a mechanism through which the effects of productivity shock on aggregate output are amplified and propagated, more in line with the empirical evidence than other related models in the literature.
Keywords: E32; E44; G3; 330; Amplification; Business cycles; Capital reallocation; Financial frictions; Propagation; Konjunkturtheorie; Investition; Verschuldungsrestriktion; Agency Theory; Real Business Cycle; Theorie